2012
DOI: 10.1111/j.1558-5646.2012.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Limits on Diversification of the Himalayan Core Corvoidea

Abstract: Within regions, differences in the number of species among clades must be explained by clade age, net diversification rate, or immigration. We examine these alternatives by assessing historical causes of the low diversity of a bird parvorder in the Himalayas (the core Corvoidea, 57 species present), relative to its more species rich sister clade (the Passerida, ∼400 species present), which together comprise the oscine passerines within this region. The core Corvoidea contain ecologically diverse species spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 102 publications
(164 reference statements)
5
45
0
Order By: Relevance
“…In the context of the proposed tempo and mode of diversification, the marginal morphological differentiation is not that unusual. Other studies have shown that elevational differences between recently diverged species generally evolve before differences in body size or feeding ecology (Kennedy et al, 2012; Price et al, 2014; Richman & Price, 1992). More broadly, these results indicate that any species concept that attempts to predict interbreeding potential simply on the basis of perceived morphological differences (Tobias et al, 2010) likely underestimates species diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the proposed tempo and mode of diversification, the marginal morphological differentiation is not that unusual. Other studies have shown that elevational differences between recently diverged species generally evolve before differences in body size or feeding ecology (Kennedy et al, 2012; Price et al, 2014; Richman & Price, 1992). More broadly, these results indicate that any species concept that attempts to predict interbreeding potential simply on the basis of perceived morphological differences (Tobias et al, 2010) likely underestimates species diversity.…”
Section: Discussionmentioning
confidence: 99%
“…from the Hemphillian (Steadman , Steadman & McKitrick , Kennedy et al . , node: Cyanocompsa and Passerina ), (iii) a fossil tentatively identified as Parulidae from the early Miocene (Kennedy et al . , Mayr , node: Parulidae, Icteridae, Emberizidae and Passerellidae), and (iv) the earliest fossil representing the crown group Passeriformes for time to most recent common ancestor (tmrca) of the root separating Acanthisitta from other passerines (Mayr , the normal prior interval was defined using the separation of New Zealand from Australia as a soft minimum; see Kennedy et al .…”
Section: Methodsmentioning
confidence: 99%
“…Recent ecological community analyses of Himalayan passerines have shed some light on adaptive processes and niche evolution. Differences among species in body size and shape as well as in foraging and feeding strategies had apparently already evolved in the early stages of SE Asian passerine radiations long before ancestors of extant species occupied their elevational niches in the respective Sino-Himalayan vegetation belts (Price 2010;Kennedy et al 2012;Price et al 2014). …”
Section: Introductionmentioning
confidence: 98%